Da’wah al-Ṣūfiyyah wa Taṭawwur al-Islām fī Indonesia: Dirāsah Ḥaula Ta’tsīr wa Musāhamah ‘Ulamā’ al-Ṣūfiyyah fī Ta’zīz al-Qiyam al-Islāmiyyah wa Nashrihā: Sufi-Based Dakwah and Islamic Propagation in Indonesia: A Study of the Influence and Contribution of Sufi Scholars in the Promotion and Dissemination of Islamic Values - Malikus Saleh; Muhammad Ichsan; Hujjatul Islam Musthafa Abdurrahman Faiz Izzatullah (Tasfiyah: Jurnal Pemikiran Islam, 2023)
The propagation of Islamic faith, or da’wah, in Indonesian archipelago had gone through a lengthy historical process. Various methods and approaches were taken to consolidate its place among the Indonesian people who were long-time believers of animism, dynamism,Hinduism, and Buddhism among others. One of such methods is the Sufi-based da’wah, which played a vital role in dissemination of Islamic faith through acculturation of its valuesinto the older beliefs. The purpose of this research is to study the Indonesian sufi community’s da’wah endeavor and the religio-cultural challenges they had faced. With the descriptive analytic and historical methods approaches, this research identifies and analyzes the works of prominent Indonesian sufi scholars which had contributed to the widespread acceptance of Islamic faith and its values. The conclusion of this research has found that there is indeed a significant influence coming from Indonesian sufi scholars toward the propagation of Islamic faith and its values, along with its consolidation and preservation therein. Thus, the result can be regarded as an effort to better understand the role of tasawuf in propagating the Islamic faith in Indonesia. Hopefully the result of this research shall deepen the understanding of the role of tasawuf in encouraging the dissemination of Islamic faith in Indonesia.